2016
DOI: 10.21010/ajtcam.v13i6.2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Diarrhoea Using Traditional Medicines: Contemporary Research in South Africa and Zimbabwe

Abstract: Background: Gastrointestinal disorders, diarrhoea in particular remain a major concern in South Africa and Zimbabwe resulting in high mortality rates when left untreated. This investigation was aimed at documenting herbal medicines used in the treatment of diarrhoea in South Africa and Zimbabwe. Materials and Methods: A review of literature on plant species used as remedies for diarrhoea in South Africa and Zimbabwe was undertaken by the use of different electronic databases such as Google Scholar, ScienceDire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
1
24
0
1
Order By: Relevance
“…However, only 60.5% of HCPs considered it necessary to report events related to herbal drugs which is a concern (Table 1). This is important in South Africa and across Africa since many such remedies are currently being used [84][85][86] and there is appropriate legislation to address this [87]. However, this attitude may reflect a general reluctance among the population to admit to seeking traditional remedies although such practices may be common especially among rural black households in South Africa [88].…”
Section: Discussionmentioning
confidence: 99%
“…However, only 60.5% of HCPs considered it necessary to report events related to herbal drugs which is a concern (Table 1). This is important in South Africa and across Africa since many such remedies are currently being used [84][85][86] and there is appropriate legislation to address this [87]. However, this attitude may reflect a general reluctance among the population to admit to seeking traditional remedies although such practices may be common especially among rural black households in South Africa [88].…”
Section: Discussionmentioning
confidence: 99%
“…These results show that L. acida extracts have potential in the management of gastrointestinal problems such as abdominal bloating, constipation, diarrhea, dysentery, and stomach ache [24,25,27,28,34,[36][37][38][39][40][41]. Research by Stark et al [71] and Maroyi [72] showed that medicinal plants have potential in the treatment of gastrointestinal disorders and the pain that is associated with the disorders.…”
Section: Antidiarrheal Activitiesmentioning
confidence: 99%
“…Proporsi obat tradisional sebagai jenis obat diare yang disimpan di rumah tangga Indonesia sebesar 19,2%, menduduki peringkat ketiga setelah adsorbans (39,4%) dan antimikroba (20,2%) (Raini and Isnawati, 2017). Sementara itu penggunaan ramuan herba untuk mengendalikan diare pada balita masih diperdebatkan meskipun praktek ini ditemukan di beberapa negara (Agunu et al, 2005;Budhathoki et al, 2016;Maroyi, 2016;Woldeab et al, 2018). Namun ada juga penelitian yang menyatakan penggunaan ramuan herba efektif dalam mengurangi frekuensi buang air besar (Anheyer et al, 2017).…”
Section: Pembahasan Sepuluh Besar Provinsi Dengan Masyarakat Melakukan Upaya Yankestrad Sendiri (Tanpa Bantuan Hattra/nakestrad/terapis)unclassified